Editorial board, information for authors, and other front matter - Jason D. Ellis (Journal of Applied Communications, 2014)
This content includes the front cover, the table of contents, editorial and other information for authors for vol. 98, no. 2 (2014) of Journal of Applied Communications
Keywords: masthead